EFFICIENT SYNTHESIS OF 2,4,5-TRISUBSTITUTED IMIDAZOLES USING SILICOTUNGSTIC ACID AS CATALYST - ANKUSH, B.P.; SHITOLE, B.V.; KUMDALE, P.G.; ADE, S.B.; SHITOLE, N.V. (Innovare Journal of Sciences, 2020)
Objective: One-pot multicomponent reactions (MCRs) that convert more than two reactants directly into their products are of interest to chemists, owing to conserving atom economy and fostering the benign synthesis of organic compound like 2,4,5-trisubstituted Imidazoles derivatives. were efficiently synthesized by the reaction of benzyl/benzoin, ammonium acetate, and aromatic aldehydes in the presence of Silicotungstic acid as catalyst in ethanol. Materials and Methods: 2,4,5-trisubstituted Imidazoles derivatives were efficiently synthesized by the reaction of benzyl/benzoin, ammonium acetate, and aromatic aldehydes in the presence of Silicotungstic acid as catalyst in ethanol under reflux. Result: The syntheses of 2,4,5-triarylimidazoles using various benzaldehyde, benzil, ammonium acetate in the presence of a catalytic amount of silicotungstic acid (7.5 % ) under reflux using ethanol as solvent. Conclusion: The attractive features of this process are mild reaction conditions, short reaction times, easy isolation of products, and excellent yields.